Flow cytometric analysis of DNA content in human ovarian cancers. - Erba, E. (Nature Publishing Group, 1989)
A total of 155 samples from 101 patients with ovarian cancer were investigated using flow cytometry to evaluate the DNA index and the percentage of cells in the various cell cycle phases. Thirty-four samples were DNA diploid tumours, while the other 121 were DNA aneuploid tumours. The DNA index was very stable in different sites and over time in the same patient. Tumour stage and ploidy were significantly associated: stages III and IV tumour stage were more likely to be DNA aneuploid. Patients with residual tumour size at first surgery greater than 2 cm had a significantly larger number of DNA aneuploid than DNA diploid tumours. The DNA index was also related to the degree of differentiation of the tumours. The percentage of cells in the S phase of the cell cycle was significantly higher in DNA aneuploid and in poorly differentiated tumours than DNA diploid and well differentiated tumours. Multivariate analysis using the Cox model showed that the DNA index and the percentage of cells in S phase were not independent prognostic variables in this study. Prospectively collected data should be accumulated before assigning the DNA index an important role as a biological prognostic factor in ovarian cancer.